Teaching idioms in the Russian lessons as a foreign language - L. Kokova, Emma (2019)
The article deals with the phraseological system of Russian in the context of teaching Russian as a foreign language. The object of attention is the technology of mastering idiomatic units by foreign students in the framework of preparatory faculties. Many methodologists believe that preparatory faculties do not prepare students for the perception and understanding of phraseological units. In the framework of this work, the methodology for presenting phraseological units to foreign students is analyzed in a number of textbooks on Russian as a foreign language.